Measuring the performance of corporate events : an empirical study of measuring practices in Finnish companies - Michael, Mari (My University, 2012)
Corporate events as an effective part of marketing communications strategy seem to be underestimated in Finnish companies. In the rest of the Europe and the USA, investments in events are increasing, and their share of the marketing budget is significant. The growth of the industry may be explained by the numerous advantages and opportunities that events provide for attendees, such as face-to-face marketing, enhancing corporate image, building relationships, increasing sales, and gathering information. In order to maximize these benefits and return on investment, specific measurement strategies are required, yet there seems to exist a lack of understanding of how event performance should be perceived or evaluated. To address this research gap, this research attempts to describe the perceptions of and strategies for evaluating corporate event performance in the Finnish events industry. First, corporate events are discussed in terms of definitions and characteristics, typologies, and their role in marketing communications. Second, different theories on evaluating corporate event performance are presented and analyzed. Third, a conceptual model is presented based on the literature review, which serves as a basis for the empirical research conducted as an online questionnaire. The empirical findings are to a great extent in line with the existing literature, suggesting that there remains a lack of understanding corporate event performance evaluation, and challenges arise in determining appropriate measurement procedures for it. Setting clear objectives for events is a significant aspect of the evaluation process, since the outcomes of events are usually evaluated against the preset objectives. The respondent companies utilize many of the individual techniques that were recognized in theory, such as calculating the number of sales leads and delegates. However, some of the measurement tools may require further investments and resources, thus restricting their application especially in smaller companies. In addition, there seems to be a lack of knowledge of the most appropriate methods in different contexts, which take into account the characteristics of the organizing party as well as the size and nature of the event. The lack of inhouse expertise enhances the need for third-party service-providers in solving problems of corporate event measurement.